A SYNONYMIZED NOMENCLATURE FOR CALCIFIED SPONGES - Zhuravlev A.Y.; Debrenne F.; Wood R.A. (My University, 1990)
A synonymized nomenclature for calcified sponges (archaeocyaths, stromatoporoids, chaetetids, sphinctozoans and pharetronids) is here presented to enable comparison of suggested homologous structures.